Dietary and Lifestyle Factors Modulate the Activity of the Endogenous Antioxidant System in Patients with Age-Related Macular Degeneration: Correlations with Disease Severity - Zofia Ulańczyk; Aleksandra Grabowicz; Elżbieta Cecerska-Heryć; Daria Śleboda-Taront; Elżbieta Krytkowska; Katarzyna Mozolewska-Piotrowska; Krzysztof Safranow; Miłosz Piotr Kawa; Barbara Dołęgowska; Anna Machalińska (Antioxidants, 2020)
Age-related macular degeneration (AMD) is a common cause of blindness in the elderly population, but the pathogenesis of this disease remains largely unknown. Since oxidative stress is suggested to play a major role in AMD, we aimed to assess the activity levels of components of the antioxidant system in patients with AMD. We also investigated whether lifestyle and dietary factors modulate the activity of these endogenous antioxidants and clinical parameters of disease severity. We recruited 330 patients with AMD (39 with early, 100 with intermediate and 191 with late form of AMD) and 121 controls in this study. At enrolment, patients’ dietary habits and physical activity were assessed, and each study participant underwent a thorough ophthalmologic examination. The activity of several components of the antioxidant system were measured in red blood cells and platelets using both kinetic and spectrophotometric methods. Patients with AMD consumed much lower levels of fatty fish and eggs than the control group (p = 0.008 and p = 0.04, respectively). In the nAMD group, visual acuity (VA) correlated positively with green vegetable consumption (Rs = +0.24, p = 0.004) and omega-3-rich oil intake (Rs = +0.17, p = 0.03). In the AMD group, the total physical activity MET score correlated positively with VA (Rs = +0.17, p = 0.003) and correlated negatively with the severity of AMD (Rs = −0.14, p = 0.01). A multivariate analysis of patients and controls adjusted for age, sex, and smoking status (pack-years) revealed that AMD was an independent variable associated with a lower RBC catalase (β = −0.37, p < 0.001) and higher PLT catalase (β = +0.25, p < 0.001), RBC GPx (β = +0.26, p < 0.001), PLT GPx (β = +0.16, p = 0.001), RBC R-GSSG (β = +0.13, p = 0.009), PLT R-GSSG (β = +0.12, p = 0.02) and RBC GSH transferase (β = +0.23, p < 0.001) activity. The activities of components of the antioxidant system were associated with disease severity and depended on dietary habits. The observed substantial increase in the activity of many critical endogenous antioxidants in patients with AMD further indicates that the required equilibrium in the antioxidant system is disturbed throughout the course of the disease. Our findings explicitly show that a diet rich in green vegetables, fish and omega-3-rich oils, supplemented by physical exercise, is beneficial for patients with AMD, as it might delay disease progression and help retain better visual function.